Improving Sharaf Memorization Through Al-Bidayah Method Book - Hidayat, Abd Khamid; Rizal, Hasan Syaiful; Hasyim, Mochamad (FONDATIA, 2024)
This study aims to evaluate the effectiveness of Al-Bidayah method book in improving sharf learning for students of Madrasah Diniyah Darut Taqwa. This study used a pre-experimental design with one group pre-test and post-test. The sample of this study amounted to 20 fourth grade students of Madrasah Diniyah Darut Taqwa in Pasuruan. The results showed that the Al-Bidayah method book was effective in increasing the memorization of sharaf, with an increase in the average post-test score by 18.15 points compared to the pre-test score. This study successfully proved that the use of learning theory from the Al-Bidayah method book is effective in improving students' understanding of sharf science, with consistent and statistically significant results.